Private insurance, public welfare, and financial markets - Heide, Arjen van der,Kohl, Sebastian (Max Planck Institute for the Study of Societies, 2022)
Contemporary capitalist societies use different institutions to manage economic risks. While different public welfare state and financial institutions (banks, capital markets) have been studied across coordinated and liberal market economies, this paper adds the private insurance sector to the study of countries' security arrangements, following up on Michel Albert's classical distinction between Alpine and Maritime insurance cultures. Building on extensive new insurance data collections (1880-2017) and institutional analysis, this paper corroborates the long-run historical existence of two worlds of private insurance. Maritime countries (USA, GBR, CAN) developed much bigger life and non-life insurance earlier, with no state-associated insurance enterprises and riskier investments steered towards financial markets. Alpine insurance (AUT, DEU, CHE), by contrast, was initially smaller, with strong state involvement, a significant reinsurance tradition and relatively heavy investments in mortgages and property, due to economic and financial backwardness. We argue that the larger and more
urn:nbn:de:101:1-2022101214452161698727
Keywords: Graue Literatur; financial development; historical comparison; insurance; varieties of capitalism; welfare; finanzielle Entwicklung; historischer Vergleich; Spielarten des Kapitalismus; Versicherungen; Wohlfahrtsstaat